“When Boys Looked Like Girls and Girls Looked Like Boys”: Interferences in the Music and Fashion World of the British 1980s – The Case of the New Romantics and their Contemporary Echoes - Julie MORÈRE (E-REA)
The creativity of fashion and the music world often relies on transfers and collaborations in which fashion designers and music celebrities interact to feature a common project. In Britain, New Romanticism was one of the 1980s musical movements most characterised by eccentric fashion experiments that were entirely part of the artistic performance and addressed cross-dressing issues. Documenting the gender-bending club youth and stars of the London underground scene, Derek Ridgers, Graham Smith or Anita Corbin have showed how fashion challenged normative dress codes and introduced a form of social disruption through the use of clothing. Magazines such as i-D questioned the hybrid style of documentary and fashion photography which shaped British identity and is still at work today. This paper explores the endless possibilities of the crossovers often found in music and fashion photography, focusing on the rejection of a simplistic reduction of gender to male and female opposites.